Microplastics in a salt-wedge estuary: Vertical structure and tidal dynamics. (November 2020) - Defontaine, Sophie; Sous, Damien; Tesan, Javier; Monperrus, Mathilde; Lenoble, Véronique; Lanceleur, Laurent
Abstract: The abundance and distribution of microplastics in estuaries have been barely documented, and generally without accounting for the vertical structure in the water column. This study presents the very first data on the occurrence and distribution of microplastics in the Adour Estuary, SW France. The experimental data set was complemented by numerical simulations to gain understanding of the behaviour of suspended microplastics. Microplastics were found throughout the water column with a mean abundance of 1.13 part / m 3 . Films and fragments were the most abundant types of particles collected. Numerical simulations demonstrated that vertical distribution of microplastics in the water column is highly dependent on particle characteristics and on the local hydrodynamics. The main trend is that neutrally-buoyant microplastics are easily flushed out while heavier microplastics are prone to entrapment in the estuary, in particular under low discharge conditions. The present study suggest that estuaries could be a sink of microplastics. Highlights: First analysis of microplastics throughout the estuary water column inside Combined field sampling experiments and 3D numerical modelling Microplastics were detected in the whole water column during the samplings. Microplastic features, discharge and tide effect govern microplastic dispersion Results suggest that microplastics may be trapped on the estuary bed.